Evaluation of sensory characteristics and rheological properties in chocolate coating with different percentages of cocoa and milk mixture - Ramirez Arroyo, Yajayra (2025)
The chocolate market exceeded 206 billion dollars, with milk chocolate standing out. Chocolates with different percentages of cocoa (50%, 60%, 70%, 80%) and milk mixture (milk powder, whey, maltodextrin) were evaluated using a randomized design with eight treatments and three replicates. The physicochemical analyses showed that the milk mixture toppings had a moisture content of 0.8% to 1%, pH of 3.5 to 4.1, °Brix between 69 and 72.5, and fat content of 20% to 36%. The toppings without milk mixture showed higher moisture (1% to 1.5%) and fat content from 17.21% to 37.5%. In terms of color, the milk-mixed toppings were lighter, with greater variation in L*, a* and b* values. Rheological analyses revealed significant differences in the fluidity parameters (n and K), with values that varied depending on the amount of cocoa and the milk mixture, evidencing changes in the texture and viscosity of the chocolate. The study reveals that cocoa and milk mixture influence the color, texture and flavor of chocolate. Milk-mixed coatings are lighter and less viscous, while non-milk-mixed coatings are more resistant. Cocoa and dairy blend affect chocolate color, texture and flavor, highlighting fatty, sweet, sour and bitter notes.